Genetic Diversity among Yersinia enterocolitica Isolated from Chicken and Fish in and around Coimbatore City, India. - Seshadhri Shanmugapriya; Thangavel Senthilmurugan; Thangavelu Thayumanavan (Tehran University of Medical Sciences, 2014)
Yersinia enterocolitica is rapidly emerging worldwide as an enteric pathogen and has become a major cause of diarrhea even in developed countries. The aim of this study was to characterize and genetic diversity analysis among Y. enterocolitica strains isolated from fish and chicken sources.From 44 strains, 55% (24 strains) found to be positive for Y. enterocolitica by colony morphology, biochemical tests and 16S rRNA. We investigate the diversity of Y. enterocolitica by hemolytic activity, antimicrobial resistance, RAPD, ERIC and REP-PCRs PCR, profiling of outermembrane proteins and lipopolysaccarides.Forty one percent of the strains were found to be the producers of haemolysin at 37 °C but not at 28 °C. All the isolates were exhibiting multi-drug resistance and found sensitive to chloramphenicol, and resistant to ciprofloxacin and amoxicillin. Eight, eleven and twelve different genotypic patterns were observed in RAPD, ERIC and REP-PCRs respectively. Five isolates have produced high molecular weight protein (HMWP) with a molecular weight of 150 - 220 kDa. Mostly LPS produce identical profiles, 22 strains have produced smooth LPS, while 2 strains have produced the rough LPS pattern.Genotyping tools strongly confirm the co-existence wide genetic diversity among the strains tested. By using any or the combination of these molecular tools, epidemiological investigation on Y. enterocolitica could be elucidated effectively. These results showed that the REP-PCR is more informative and discriminative than other for analysis of Y. enterocolitica diversity.